(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Adolescence is a period of a child turned into an adult. Adolescence women two years earlier than men. Data pornography, the adolescent is a large population than the population of the word. WHO and some other word body called on all countries of Southeast Asia to provide its commitment to observe and protect the needs of adolescents and information, skills, service, and safe environment and supportive of essential reproductive health. The reproductive period in the life of a woman who started from menarche until menopause occurs. The menstrual period they are sometimes accompanied by disturbances such as premenstrual syndrome (PMS). It is estimated that 80-10% of women do not have PMS, and approximately 25-40% have PMS. Most women experience PMS symptoms in a long period. The symptoms are of an emotional outburst in the form of anger, high sensitivity, sad, lonely, until the desire to commit suicide. Is research target is to know the relation of between level of knowledge of syndrome premenstrual with the handling of syndrome premenstrual of at adolescent of age 12-15 year in SMP PGRI Bantul. Methods: The study was observational analytic with the cross-sectional approach. The samples were all students SMP PGRI Bantul amounting to 138 students and measuring the level of knowledge and handling of premenstrual syndrome using questioner. Analysis of data used univariate and bivariate analysis with chi-square. Result: There was a relationship between the level of knowledge about premenstrual syndrome with the handling of premenstrual syndrome in adolescents age 12-15 years in the SMP PGRI Bantul with the value of P=0,000. Conclusion: There was a relationship between the level of knowledge about premenstrual syndrome with the handling of premenstrual syndrome treatment. Key words: level of knowledge, premenstrual syndrome, adolescent